The Basis for the Judge's Consideration of the Power of Testimony of Minors in Proving the Crime of Rape (Sibolga District Court Decision Study No.39/Pid.Sus/2016/Pn Sbg.) - Desi Putri Br Barus (CERED Indonesia Institute, 2022)
Children are the future and the nation's next generation who have limitations in understanding and protecting themselves from various influences of the existing system. Sexual violence against children often occurs, so it impacts the child's physical and psychological aspects, which can be carried over to the child's maturity and interfere with the child's development. The description of a child as a victim can use in proving a crime. The method used in this study is normative juridical research. The nature of the research used is descriptive analysis, and data analysis carries out qualitatively using library data collection techniques. The results of this study found that the position of a child as a witness in a criminal case has legally recognized in the Criminal Procedure Code. However, the statement of a child witness cannot be accounted for in criminal law by the provisions of Article 160, paragraph (3) of the Criminal Procedure Code, Article 185, paragraph (7) of the Criminal Procedure Code, and Article 184 Criminal Procedure Code. The strength of the child's testimony can be said not to have reliable evidentiary power to determine whether the defendant has committed a crime but rather to strengthen the judge's conviction. In the judge's consideration of sentencing decisions, in general, the information given by the child is used by the judge as a guide and reinforcement of other legal evidence based on adjustments and links with evidence and facts that occurred in court, which use as a reinforcement for the judge's conviction and as a consideration in imposing a criminal sentence. In giving sentencing decisions in the decision file No.39./Pid.Sus/2016/PN Sbg the statement of the child as a victim witness adds to the confidence of the Panel of Judges.